Middle Byzantine glazed pottery from Nauplio: an overview - Vassiliou, Anastasia (Journal of Greek Archaeology, 2022)
From the 1970s up to the present day the Greek Archaeological Service has carried out several rescue excavations at the castle and in the Lower town, which have yielded interesting ceramic material. The aim of this paper is to present an overview of the unpublished Middle Byzantine glazed pottery identified in the other rescue excavations conducted by the Greek Archaeological Service.